Researches of the Dynamics of Cutting Through of the Material by a Water-Ice Jet - Burnashov Mikhail (EDP Sciences, 2021)
Hypersonic ice abrasive water jet cutting is a subject of great attention in the production industry. The paper presents some mathematical equations for determining energy parameters of ice water jet cutting. The mathematical model presented in the article can be used for developing a technology for cutting, strengthening, cleaning, or destructing various materials.